Tradução, adaptação transcultural e validação da versão brasileira de uma escala de Saúde Bucal para pessoas com Síndrome de Down - Karina Bonanato Teixeira (2011)
The validity of questionnaires to measure oral health is important for epidemiological investigation. The oral health scale for people with Down syndrome has been developed to assess oral health status of individuals with four or more years old with Down syndrome (DS). The aim of this study is to perform the cross-cultural adaptation and validation of the scale for the Brazilian Portuguese language. The scale was translated by three independent translators. Careers of people with Down syndrome, health and education professionals who work with these individuals participated in the process of the scale cross-cultural adaptation. The Portuguese version obtained underwent back-translation and this version was compared to the original one by the author of the instrument. The final version in Portuguese was tested in 157 caregivers of people with Down syndrome. For the tests of validity, individuals with Down syndrome were evaluated clinically for malocclusion through the Dental Aesthetic Index (DAI), for dental caries through the index of decayed missing and filled (DMFt), for periodontal health through plaque index (IP) and gingival (IG). Two examiners were calibrated for each of the oral health status. People with DS were selected from institutions that assist people with Down syndrome and their caregivers in Brazil. The internal consistency was assessed by Cronbach's alpha and test-retest reliability by intraclass correlation coefficient (ICC). The average score of the scale was 18.6 [± 9.0]. Internal consistency ranged from 0.49 to 0.80 and reproducibility ranged from 0.78 to 0.88. The DAI ranged from 19 to 123, average 44.23 [± 19.35]. DMFt ranged from zero to 32, mean 6.04 [± 8.10]. The IP ranged from 0.16 to 2.45, mean 1.09 [± 0.55] and IG ranged from zero to 2.54, mean 1.09 [± 0.61]. Construct validity was verified by significant correlations between the scale scores and clinical indicators such as DAI (p <0.05). The correlation between the caregiver schooling and the scale was also used to verify the construct validity (p <0.05). Discriminant validity was ascertained through assossiation between the scale answered for people with Down syndrome and those without the syndrome (p <0.05). The questionnaire proved to be a valid instrument. The present study demonstrated that the scale is applicable to people with Down syndrome in Brazil.